(untitled) (International Journal of Engineering and Computer Science, 2017)
The rapidly growing energy consumption has raised concerns over exhaustion of energy resources and its impacts on the environment. The global contribution towards energy consumption of the developed countries including residential and industrial sector has steadily increased from 20% to 40%. For this reason, it is of utmost importance to manage and monitor the energy consumption and making it cost efficient for small and large scale industries, as industrial sector contributing the higher rate of energy consumptions. Therefore, the system is proposed to remotely manage and monitor the Energy utilization considering various parameters and generating the reports, log data for analytics. Thus, reducing fault logs providing live alerts by real time monitoring with a better performance and efficiency, finally reducing the cost. The approach is to ensure a robust system on aspects such as measure, store and report via high quality components and redundancies in the system design.